Fatal traumatic brain injuries in the construction industry, 2003−2010. Issue 3 (4th January 2016) - Konda, Srinivas; Tiesman, Hope M.; Reichard, Audrey A.
Abstract : Background: Research on fatal work‐related traumatic brain injuries (TBIs) is limited. This study describes fatal TBIs in the US construction industry. Methods: Fatal TBIs were extracted from the Bureau of Labor Statistics Census of Fatal Occupational Injuries. Results: From 2003 to 2010, 2, 210 fatal TBIs occurred in construction at a rate of 2.6 per 100, 000 full‐time equivalent (FTE) workers. Workers aged 65 years and older had the highest fatal TBI rates among all workers (7.9 per 100, 000 FTE workers). Falls were the most frequent injury event (n = 1, 269, 57%). Structural iron and steel workers and roofers had the highest fatal TBI rate per 100, 000 FTE workers (13.7 and 11.2, respectively). Fall‐related TBIs were the leading cause of death in these occupations. Conclusions: A large percentage of TBIs in the construction industry were due to falls. Emphasis on safety interventions is needed to reduce these fall‐related TBIs, especially among vulnerable workers. Am. J. Ind. Med. 59:212–220, 2016. Published 2016. This article is a U.S. Government work and is in the public domain in the USA.